2018
DOI: 10.1073/pnas.1715922115
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum acyltransferase with prokaryotic substrate preference contributes to triacylglycerol assembly in Chlamydomonas

Abstract: Understanding the unique features of triacylglycerol (TAG) metabolism in microalgae may be necessary to realize the full potential of these organisms for biofuel and biomaterial production. In the unicellular green alga a chloroplastic (prokaryotic) pathway has been proposed to play a major role in TAG precursor biosynthesis. However, as reported here, contains a chlorophyte-specific lysophosphatidic acid acyltransferase, CrLPAAT2, that localizes to endoplasmic reticulum (ER) membranes. Unlike canonical, ER-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
(83 reference statements)
1
44
0
Order By: Relevance
“…Lysophosphatidic acid acyltransferase (LPAAT) mediates the second acylation leading to the formation of phosphatidic acid (PA). C. zofingiensis contains three putative LPAAT isoforms: Cz16g02090, a homologue of C. reinhardtii chloroplastic LPAAT (LPAAT1) (Yamaoka et al ., ) , Cz04g14150, a homologue of C. reinhardtii ER LPAAT (LPAAT2) (Kim et al ., ) and Cz10g20070. The former two were greatly upregulated (~3.9‐ and 4.7‐fold, respectively), whereas the third gene showed just a slight upregulation (<2‐fold) upon ND (Figure b and Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Lysophosphatidic acid acyltransferase (LPAAT) mediates the second acylation leading to the formation of phosphatidic acid (PA). C. zofingiensis contains three putative LPAAT isoforms: Cz16g02090, a homologue of C. reinhardtii chloroplastic LPAAT (LPAAT1) (Yamaoka et al ., ) , Cz04g14150, a homologue of C. reinhardtii ER LPAAT (LPAAT2) (Kim et al ., ) and Cz10g20070. The former two were greatly upregulated (~3.9‐ and 4.7‐fold, respectively), whereas the third gene showed just a slight upregulation (<2‐fold) upon ND (Figure b and Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…pathway by Chlamydomonas because it lacks thylakoid lipids with 18C acids at the sn-2 position [113,244,245]. But this has recently been challenged by the discovery of an ERlocated lysophosphatidate acyltransferase (LPAAT) with substrate preference of 16C rather than an 18:0 FA at its sn-2 position in C. reinhardtii [247]. In addition, a chloroplast pathway for TAG formation in C. reinhardtii was recently reported [248].…”
Section: The Kennedy Pathwaymentioning
confidence: 99%
“…Fan et al (2011) demonstrated that nitrogen starved Chlamydomonas cells accumulated significantly higher amount of C16 fatty acid moieties, which is accounted for up to 90% of the total TAG implied the substrate specificity of plastidial LPAAT toward C16:0 fatty acid moieties rather than ER-localized LPAAT (Fan et al, 2011). These studies have provided the crucial role of subcellular organelles in governing the TAG biogenesis and our results which depicted that C16:0-fatty acids were the predominant fatty acid composition compared to other fatty acids, thereby provoking the necessity to interrogate the role of subcellular compartments in governing lipogenesis in a growthphase dependent manner (Kim et al, 2018).…”
Section: Bioprocess Monitoring and Lipidomic Analyses Revealed The Pomentioning
confidence: 51%